* Spasticitet er en kropslig variation: En cripteoretisk analyse af danseforestillingen SPLASTIC - Flyvbjerg Kornerup, Ellen; Flyvbjerg Hesthaven, Signe (Peripeti, 2018)
The dance performance SPLASTIC celebrates the potential of spastic movement. This article asks if the performance also avoids reproducing normative narratives about the norm-challenging body. The answer is: Not entirely. But the curious, ugly and unproductive movements allow the dancers to counter bodily normativity and efficiency demands and makes visible the potential.